1985
DOI: 10.1021/jf00061a022
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and anaerobic degradation of aldicarb in soils

Abstract: Mineralization of aldicarb to C02 as well as formation of various metabolites and extractable and nonextractable 14C were measured in [14C] aldicarb-treated surface and subsurface soils. Surface soil samples were incubated under aerobic conditions, and subsurface soil samples were incubated under aerobic and anaerobic conditions. Total aldicarb, aldicarb sulfoxide, and aldicarb sulfone residue (TTR = total toxic residue) disappearance rates were also determined in soils held under aerobic conditions. These dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 9 publications
2
12
0
1
Order By: Relevance
“…Similar to the degradation patterns of some órgano sulfur pesticides such as aldicarb (Bromilow et al, 1980;Coppedge et al, 1967;Ou et al, 1985;Smelt et al, 1978) and phorate (Talekar et al, 1977;Walter-Echols and Lichtenstein, 1978), we found that P in Arredondo sand was rapidly oxidized to PSO which was further oxidized to PSO. (Figure 2).…”
Section: Because Of Low Levels Of Extractable C Remaining In Arredondsupporting
confidence: 68%
“…Similar to the degradation patterns of some órgano sulfur pesticides such as aldicarb (Bromilow et al, 1980;Coppedge et al, 1967;Ou et al, 1985;Smelt et al, 1978) and phorate (Talekar et al, 1977;Walter-Echols and Lichtenstein, 1978), we found that P in Arredondo sand was rapidly oxidized to PSO which was further oxidized to PSO. (Figure 2).…”
Section: Because Of Low Levels Of Extractable C Remaining In Arredondsupporting
confidence: 68%
“…Technical grade carbofuran (99% purity), analytical grade carbofuran phenol (99.3% purity), uniformly ring‐labeled (URL) 14 C‐carbofuran and carbonyl‐labeled (CAL) 14 C‐carbofuran were gifts from FMC Corporation (Princeton, NJ, USA). Prior to use, the two radiolabeled compounds were purified to >98% radiopurity by thin‐layer chromatography (TLC) using preparative silica gel G TLC plates [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Prior to use, the two radiolabeled compounds were puri¢ed to s 98% radiopurity by thinlayer chromatography (TLC) using preparative silica gel G TLC plates [7,8].…”
Section: Chemicalsmentioning
confidence: 99%